Analisi Filosofis Hakikat Pendidik Dalam Islam - Muhamad Faizul Amirudin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
The existence of educators in education is crucial, because the obligation not only to transform knowledge (knowledge) but also required to internalize the values ​​(value / qimah) on the learner. In this paper discussed about the meaning educators, educators in Islamic education, educator according to Muslim philosophy, competence educators in Islamic education, duties, responsibilities and rights of educators and code of ethics educators. The nature of the educator is Allah that teaches science to human beings and others have an obligation for him to transferring that knowledge to others to benefit.